Networks in Berlin's Music Industry – A Spatial Analysis - Marco Mundelius; Wencke Hertzsch (European Regional Science Association (ERSA), 2005)
In addition to a distinct regional concentration of the branch in a few, large metropolitan areas in Germany, Berlin shows inner-city (inner-regional) concentrations of the music industry and its players linked with the value chain as well as branch-relevant institutions. By means of a written survey of companies in the media and IT industries in Berlin and Brandenburg plus expert interviews, an analysis of the Berlin music branch, regarding its spatial as well as organizational concentration and how this concentration is perceived by companies, has been carried out. A comparison of the results within the branch and with the Brandenburg region can be made on the basis of a differentiation of the media branch in the analysis. This analysis found that creative milieus are of particular importance as they perform the role of being the driving force in developing the field of music. Therefore this paper examines spillovers into this industry, as a first step of spatial concentration in terms of networks of music companies, institutions, and the specific and innovative milieu and the geographical dimension of knowledge. Furthermore, evidence has been found through the use of economic and socio-cultural indicators. Urbanization economies become especially clear (apparent) for the region in the examination of Berlin's music industry with their intersectoral integration and cross-sectoral stimilus to settlement and formation of companies.
Keywords: 330